Réponses

2014-01-23T17:32:15+01:00
17. Factoriser = transformer en multiplication
A= t² +81 + 18t
A = t² + 2*9 t +9²
A = ( t +9 )²

B = 4x² - 4xy +y²
B = (2x- y)²

C = 81 + 16y² - 72y
c = 16 y² - 2*4*8 y + 9²=
C = (4y -9)²

D = x² + 36 - 12x
D = x² -2*6 x + 6²
D = (x - 6)²

E = 4/9 p² +4/3 pq +q²
E = (2/3 p+q)²

F = π² + 10 π +25
F = (π +5)²

18.
A = x² -16
A = (x-4) (x+4)

B= 1-y²
B = (1-y) (1+y)

C = 100x²-9
c = (10x- 3) ( 10x+3)

D= 36 - 81 z²
D= (6-9z) (6+9z)

E= 4π² - 25
E = (2π-5) (2π+5)

F= (t+3)²- 16
F= (t+3-4) (t+3+4)
F = (t-1) (t+7)

G= (2x+1)²- 25
G = (2x+1 -5) (2x +1 +5)
G = (2x -4) ( 2x +6)

H = (3i+7)² - (i+5)²
H = (3i +7 - i -5) ( 3i+7 +i+5)
H = (2i +2) (4i+12)